Peran Majelis Pengawas Notaris Daerah (MPN) Dalam Melaksanakan Pembinaan Dan Pengawasan Notaris Di Kabupaten Jombang - Zumrotul Muniroh; Rini Winarsih; Romlan Prasodjo (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The legal profession is a profession that prioritizes moral values. One of them is a Notary as a public official who is authorized to make authentic deeds and other authorities are regulated in the Notary Law. Deviations are often found by Notaries. If the deviation extends from its ideal form, it will result in diminishing public trust in Notaries. In this study, the problems raised are how to implement guidance and supervision, as well as the role of the Regional Notary Supervisory Board towards Notaries in Jombang Regency. This study uses normative legal research methods, namely literature studies and unstructured interviews. The implementation of guidance and supervision by the Regional Notary Supervisory Board towards Notaries in Jombang Regency is related to 3 things, the existence of complaint reports from the public, examination of Notary protocols, and examination of other legal facts. Supervision carried out by the Regional Notary Supervisory Board is important because it oversees the enforcement of Law Number 30 of 2004 and its Amendments, namely Law Number 2 of 2014 concerning Notary Positions and the Notary Code of Ethics.